Six-Week Interval Between Preoperative Radiation and Surgery Is Associated With Fewer Major Wound Complications in Soft Tissue Sarcoma. (July 2020) - Collier, Christopher D.; Su, Charles A.; Reich, Michael S.; Tu, Leigh-Anne; Getty, Patrick J.
Abstract : Objectives: A total of 30% to 40% of soft tissue sarcoma (STS) patients develop major wound complications (MWCs) after preoperative radiation (preRT). The optimal preRT-surgery interval and its association with MWCs is unknown. This study investigated whether a longer preRT-surgery interval is associated with fewer MWCs compared with historical controls. Methods: All patients treated by a single surgeon after preRT with limb-sparing wide resection for extremity and trunk STS were retrospectively reviewed from 2004 to 2014. The primary outcome was MWCs defined as a secondary operation, invasive procedure, wound packing, or readmission for wound care. Secondary outcomes of local recurrence and survival were followed and independent variables were analyzed for an association with MWCs. Results: Fifty-four patients were included with a median follow-up of 32 months and age of 61 years. The majority of tumors were deep (91%), large (median size of 11 cm), high grade (78%) and within the lower extremity (78%). The median preRT-surgery interval was 43 days and 80% of patients received surgery 35 to 49 days after radiation. MWCs were observed in 15% of patients and 88% occurred within 40 days. Predictors for MWCs on multivariate analysis were peripheral vascular disease ( P =0.03), location in the medial compartment of the thigh ( P =0.03), and neurovascular involvement ( P =0.03). Conclusions: This study presents a cohort of STS patients with an extended preRT-surgery interval of ~6 weeks. MWCs in this population occurred at a lower rate than historical controls. Overall these findings support the exploration of a longer interval to reduce MWCs and their associated morbidity.